Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1097/bot.0000000000000765
|View full text |Cite
|
Sign up to set email alerts
|

Clavicular Refracture at the Site of Angular Malunion in Young Athletes

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…23 In the NFL, players with nonoperatively managed, displaced midshaft fractures had a reported refracture rate of 57% compared with 5% with plate fixation. 26 Likewise, refracture at the site of a united angular malunion has been reported in adult athletes 11 and pediatric patients at a significantly increased incidence. 22 A recent systematic review of primarily level 2 and level 3 studies reported significantly longer return times and longer return to preinjury level of sport for nonoperatively managed displaced midshaft fractures compared with surgically managed fractures confirmed by meta-analysis of the study results.…”
Section: Discussionmentioning
confidence: 99%
“…23 In the NFL, players with nonoperatively managed, displaced midshaft fractures had a reported refracture rate of 57% compared with 5% with plate fixation. 26 Likewise, refracture at the site of a united angular malunion has been reported in adult athletes 11 and pediatric patients at a significantly increased incidence. 22 A recent systematic review of primarily level 2 and level 3 studies reported significantly longer return times and longer return to preinjury level of sport for nonoperatively managed displaced midshaft fractures compared with surgically managed fractures confirmed by meta-analysis of the study results.…”
Section: Discussionmentioning
confidence: 99%
“…Shortening, in particular, has been suggested to Copyright @ 2020 JPOSNA www.jposna.org correlate with decreased range of motion, scapular dyskinesis, and decreased functional scores in adults, though controversy remains as to the degree to which shoulder function is truly affected. [55][56][57][58][59] Malunion has been associated with increased risk of refracture in young adults 60 but likely requires further analysis in children and adolescents. Skeletally immature patients with clavicle fracture malunions do not appear to develop clinically significant loss of shoulder motion, strength, or discomfort.…”
Section: Complicationsmentioning
confidence: 99%
“…Two patients with delayed surgical treatment were excluded from the study leaving 17 males (80.9%) and four females (19.1%). The mean age at onset was 15.9 (11)(12)(13)(14)(15)(16)(17)(18)(19) years. Radiographic union was achieved in all patients by the 6-week follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Masnovi et al demonstrated significantly increased refracture rates (26%) in angulated fractures compared with completely displaced fractures (6%) and clavicle fractures as a whole (1.6%) in pediatric clavicle fractures [10]. Furey et al recently published a study in adolescent athletes who had refractures at the site of angular malunion following nonoperative treatment [11]. Refracture rates with nonoperative…”
Section: Discussionmentioning
confidence: 99%